2010
DOI: 10.1007/s11604-009-0376-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the inequalities in radiotherapy health resources in Japan: comparison of the Hokkaido-Tohoku and Tokyo districts

Abstract: Geographical inequalities in radiotherapy health resources tended to be larger in the Tokyo district than in the Hokkaido-Tohoku district. It is expected that the radiotherapy system will be substantially improved by the Basic Plan to Promote Cancer Control Programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Although 20% of the population live in rural regions in the U.S., only 3% of oncology professionals are in these regions (Kirkwood et al 2014). In Japan, the number of oncology professionals is also higher in urban than in rural regions, which have hardly any (Ohba et al 2010;Yamamoto and Tamura 2012;Fukuda et al 2018). As the number of patients with cancer has been steadily increasing in Japan, with the aim to provide an equal cancer treatment throughout the country, the Japanese government approved the Cancer Control Act in 2007 and the Basic Plan to Promote Cancer Control program was launched (Ministry of Health, Labour and Welfare 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although 20% of the population live in rural regions in the U.S., only 3% of oncology professionals are in these regions (Kirkwood et al 2014). In Japan, the number of oncology professionals is also higher in urban than in rural regions, which have hardly any (Ohba et al 2010;Yamamoto and Tamura 2012;Fukuda et al 2018). As the number of patients with cancer has been steadily increasing in Japan, with the aim to provide an equal cancer treatment throughout the country, the Japanese government approved the Cancer Control Act in 2007 and the Basic Plan to Promote Cancer Control program was launched (Ministry of Health, Labour and Welfare 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, Toyabe [ 6 ] compared the Gini coefficient with other inequality indices such Atkinson index and Theil index to assess the distribution of physicians where all the indices generated relatively the same findings. Also in Japan, Ohba et al [ 8 ] determined that the inequality of radiotherapy health resources in Tokyo district is higher than in the Hokkaido-Tohoku by using the Gini coefficient. Furthermore, Matsumoto et al [ 7 ] used Gini coefficient to validate that primary care physicians’ distribution in Britain is relatively equal than in Japan.…”
Section: Methods and Datamentioning
confidence: 99%
“…Ohba et al [ 8 ] compared the geographical inequalities of radiotherapy resources in two districts of Japan, Hokkaido-Tohoku and Tokyo. Results demonstrated that the inequality is higher in the Tokyo district.…”
Section: Introductionmentioning
confidence: 99%
“…The GC is widely used to measure inequity in income distribution. Several research groups have applied this method to evaluate health resource distribution; for example, physicians or medical facilities [2628]. We adopted the GC as an indicator to refer to regional maldistribution of physicians/specialists to aid evaluation of inequity of human resources by SMCA.…”
Section: Methodsmentioning
confidence: 99%